Adjustable Optical Slit Based on the Phase Type Spatial Light Modulator - Di Wang; Chao Liu; Qiong-Hua Wang (IEEE Photonics Journal)
In this paper, we propose an adjustable optical slit based on a phase type spatial light modulator (SLM). The adjustable optical slit consists of two polarized beam splitters and one SLM. The SLM is used to modulate the phase of light. A phase grayscale with specific structure is produced, where the middle phase is 0 and the phase on both sides is π. By changing the width of the slit grayscale, we can adjust the width of the slit easily. Our experiment shows that one-dimensional (1-D) slit and 2-D mask can be realized and the slit width can be tuned accordingly. The results verify its feasibility. The adjustment accuracy of slit can reach several microns, and the slit can also be laterally translated. The proposed device can be used not only in optical system or holographic display to improve the quality of the image, but also in spectrometers to select the specific spectral feature.